2016
DOI: 10.4081/jlimnol.2016.1430
|View full text |Cite
|
Sign up to set email alerts
|

Thermal structure and circulation in Lake Chapala, Mexico

Abstract: This study analyzed and discussed the instrumental measurements of temperature and currents made on January 10, 2007,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Lake Chapala is located between Jalisco and Michoacán, Mexico (20° 15' N and 103° 01' W). Lake Chapala is the largest natural lake in Mexico having an average depth of 6 m, with a maximum depth near 11 m [35]. Lake Chapala (Figure 2) covers an area of circa 1161 km 2 ; its length is over 79 km and has a width of circa 28 km.…”
Section: Lake Chapalamentioning
confidence: 99%
See 1 more Smart Citation
“…Lake Chapala is located between Jalisco and Michoacán, Mexico (20° 15' N and 103° 01' W). Lake Chapala is the largest natural lake in Mexico having an average depth of 6 m, with a maximum depth near 11 m [35]. Lake Chapala (Figure 2) covers an area of circa 1161 km 2 ; its length is over 79 km and has a width of circa 28 km.…”
Section: Lake Chapalamentioning
confidence: 99%
“…Lake Chapala and water inbound from the Lerma River supply water for industry, drinking water and irrigation. On the riverside of Lake Chapala, considerable tourism, fishing, industrial, and agricultural activities are observed [35].…”
Section: Lake Chapalamentioning
confidence: 99%
“…Furthermore, Valle de Bravo larger surface area (18.55 km2) favours wind-induced mixing depths larger than those observed in SAMO Lake, which has a significant smaller surface area (3.7 km2). An extreme example is Chapala Lake (Mexico), where its large surface area (1 112 km2) and shallowness cause a warm polymictic regime (Avalos-Cueva et al, 2016;Lind et al, 1997).…”
Section: Heat Transfermentioning
confidence: 99%
“…In Guadalajara, Jalisco the monthly average air temperature from March to May 1998 was 3-4°C higher than the climatological mean for this same season. The atmospheric relative afternoon humidity decreased from 6 to 8% [14]. Due to the intense dry season, the lake lost more than 1 m of its water level due to evaporation and the excess of water pumped to satisfy water demand from the local industry and population [8].…”
Section: Long-term Fluctuations In the Lake Levelmentioning
confidence: 99%